Endothelial progenitor cell levels in obese men with the metabolic syndrome and the effect of simvastatin monotherapy vs. simvastatin/ezetimibe combination therapy - Westerweel, Peter E; Visseren, Frank L J; Hajer, Gideon R; Olijhoek, Jobien K; Hoefer, Imo E; de Bree, Petra; Rafii, Shahin; Doevendans, Pieter A; Verhaar, Marianne C (European heart journal, 2008)
Endothelial progenitor cells (EPCs) contribute to endothelial regeneration and thereby protect against cardiovascular disease (CVD). Patients with manifest CVD have reduced EPC levels, but it is not clear if this also occurs in subjects at high CVD risk without manifest atherosclerotic disease. Therefore, we aimed to first, measure circulating levels of EPCs in subjects without manifest CVD but at high cardiovascular risk due to obesity and presence of the metabolic syndrome. Second, we evaluated the effect on EPC levels of two lipid-lowering treatments. Circulating CD34+KDR+ EPC levels were reduced by nearly 40% in obese men with the metabolic syndrome compared to non-obese healthy controls (331 +/- 193 vs. 543 +/- 164 EPC/mL, P = 0.006). In a randomized double-blind cross-over study comparing intensive lipid-lowering treatment using 80 mg simvastatin mono-treatment with combination treatment of 10 mg simvastatin and 10 mg ezetimibe, we found a similar treatment effect on EPC levels. Secondary analyses of these data suggested that both treatment regimens had increased circulating EPCs to control levels (626 +/- 428 after combination treatment, P < 0.01; 524 +/- 372 EPC/mL after monotherapy, P < 0.05). Serum levels of EPC-mobilizing factor SCF-sR correlated with reduced EPC levels and normalized concurrently with treatment. EPC levels are reduced in apparently healthy men with abdominal obesity and the metabolic syndrome, even in the absence of manifest CVD. This is important as EPCs contribute to endothelial regeneration and thereby protect against CVD. SCF-sR may be a candidate serum marker of circulating EPC levels. Treatment with low-dose statin with ezetimibe combination therapy or high-dose statin monotherapy has similar effects on the reduced EPC levels.